2022
DOI: 10.1126/sciadv.abn0707
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of somatic mutations by animal offspring

Abstract: Since 1892, it has been widely assumed that somatic mutations are evolutionarily irrelevant in animals because they cannot be inherited by offspring. However, some nonbilaterians segregate the soma and germline late in development or never, leaving the evolutionary fate of their somatic mutations unknown. By investigating uni- and biparental reproduction in the coral Acropora palmata (Cnidaria, Anthozoa), we found that uniparental, meiotic offspring harbored 50% of the 268 somatic mutat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…R. Soc. B 290: 20221766 also in the sperm, or that there was a strong correlation between the parent VAF and the sperm VAF for P + S SNVs, we would have concluded that Acropora corals developed gametes directly from those tissues [15,16]. By contrast, the occurrence of both types of patterns suggests that germ cell differentiation in corals occurs in a different manner than posited by Weismann's Germ Plasm Theory.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…R. Soc. B 290: 20221766 also in the sperm, or that there was a strong correlation between the parent VAF and the sperm VAF for P + S SNVs, we would have concluded that Acropora corals developed gametes directly from those tissues [15,16]. By contrast, the occurrence of both types of patterns suggests that germ cell differentiation in corals occurs in a different manner than posited by Weismann's Germ Plasm Theory.…”
Section: Discussionmentioning
confidence: 93%
“…If we had found only separate parent and sperm SNVs this would have shown that Acropora corals have classical Weismannian germ and somatic cell lineage differentiation at the embryonic stage, which has been suggested previously [ 17 ]. Likewise, if we had found that all parent tissue SNVs were also in the sperm, or that there was a strong correlation between the parent VAF and the sperm VAF for P + S SNVs, we would have concluded that Acropora corals developed gametes directly from those tissues [ 15 , 16 ]. By contrast, the occurrence of both types of patterns suggests that germ cell differentiation in corals occurs in a different manner than posited by Weismann's Germ Plasm Theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal colonies consisting of many modules may remain coherent entities where colony traits have the evolutionary potential to respond to natural selection (Simpson et al., 2020). Remarkably, variants may arise locally, and single modules may have some evolutionary potential (Vasquez Kuntz et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Animal colonies consisting of many modules may remain coherent entities where colony traits have the evolutionary potential to respond to natural selection(Simpson et al, 2020). Remarkably, variants may arise locally, and single modules may have some evolutionary potential(Vasquez Kuntz et al, 2022).Local modular plasticity was accompanied by significant methylome and transcriptome modifications. Our data showed a significant light-mediated change in coral morphology, a phenotypic adjustment reflected in molecular signatures of changes in growth, including soft tissue growth and biomineralization.…”
mentioning
confidence: 99%